Inhibitory effects of total saponin from Korean red ginseng via vasodilator-stimulated phosphoprotein-Ser(157) phosphorylation on thrombin-induced platelet aggregation - Lee, Dong-Ha (The Korean Society of Ginseng, 2013)
In this study, we have investigated the effects of total saponin from Korean red ginseng (TSKRG) on thrombin-induced platelet aggregation. TSKRG dose-dependently inhibited thrombin-induced platelet aggregation with IC(50) value of about 81.1 μg/mL. In addition, TSKRG dose-dependently decreased thrombin-elevated the level of cytosolic-free Ca(2+) ([Ca(2+)](i)), one of aggregation-inducing molecules. Of two Ca(2+)-antagonistic cyclic nucleotides as aggregation-inhibiting molecules, cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), TSKRG significantly dose-dependently elevated intracellular level of cAMP, but not cGMP. In addition, TSKRG dose-dependently inhibited thrombin-elevated adenosine triphosphate (ATP) release from platelets. These results suggest that the suppression of [Ca(2+)](i) elevation, and of ATP release by TSKRG are associated with upregulation of cAMP. TSKRG elevated the phosphorylation of vasodilator-stimulated phosphoprotein (VASP)-Ser(157), a cAMP-dependent protein kinase (A-kinase) substrate, but not the phosphorylation of VASP-Ser(239), a cGMPdependent protein kinase substrate, in thrombin-activated platelets. We demonstrate that TSKRG involves in increase of cAMP level and subsequent elevation of VASP-Ser(157) phosphorylation through A-kinase activation to inhibit [Ca(2+)](i) mobilization and ATP release in thrombin-induced platelet aggregation. These results strongly indicate that TSKRG is a beneficial herbal substance elevating cAMP level in thrombin-platelet interaction, which may result in preventing of platelet aggregation-mediated thrombotic diseases.